The Relationship Between the Use of AI Chatbots and High School Students’ Critical Thinking Skills and Self-Efficacy - Siva Sabila; Nur Hanifah Insani (Universitas Pendidikan Ganesha, 2026)
The development of Artificial Intelligence (AI), especially AI Chatbots, has brought significant changes in the learning paradigm by presenting adaptive, personal, and contextual learning interactions. This study aims to examine the relationship between the use of AI Chatbots in Javanese language learning and its relationship to critical thinking skills and self-efficacy of high school students. This study uses a quantitative approach with a correlational design. The research sample amounted to 462 students of SMA Negeri 9 Semarang who were selected using stratified random sampling techniques. Data were collected through an online questionnaire and analyzed using descriptive statistics and Pearson correlation tests. The results of the study show that AI Chatbots have been known and used quite widely by students in learning Javanese, although the utilization rate is still moderate. The correlation results showed a positive relationship between the use of AI Chatbots and students' critical thinking skills (r = 0.572; p < 0.01) and student self-efficacy (r = 0.542; p < 0.01). This means that the more intense the use of AI Chatbots, the higher the level of critical thinking and self-confidence of students in the learning process. Thus, the use of AI Chatbots in Javanese language learning contributes positively to improving students' critical thinking skills and self-efficacy, so teachers and schools need to implement it in a planned manner through systematic AI literacy learning strategies and training so that its use is optimal, meaningful, and responsible.